Pengaruh Persepsi Terhadap Minat Menabung Pada Produk Simpanan Wadiah (Studi Masyarakat Desa Lepang Besar Lampung Utara) - Sari, Putri Tiara; Fahlevi, Muhammad Ryan (Jurnal Iqtisaduna, 2024)
The purpose of this study was to see the effect of perceptions of the people of lepang besar village, North Lampung, on interest in saving on Islamic banking products, namely wadiah deposits. The approach in this study uses quantitative using data collection methods through distributing questionnaires with Likert scale instruments and supporting data collected through documentation techniques. Respondents in this study were 90 people from Lepang Besar Village, North Lampung. This study uses validity test analysis techniques, reliability tests, normality tests, heteroscedasticity tests, simple regression analysis, hypothesis testing using partial T tests and the Coefficient of Determination (R2). The results of this study indicate that the Perception variable (X) has a positive and significant effect on Interest in Saving (Y) with a significance value of 0.000 (<0.05) and a calculated t value of 11.464 (> 1.662). Based on the results of the Coefficient of Determination (R2) test, it is known that the effect of perception on saving interest is 59.9%. The results showed that perception has a positive and significant effect on interest in saving. Which means that people's perceptions of Islamic banks affect people's interest in saving at Islamic banks.